Faktor-Faktor yang Mempengaruhi Konsumen dalam Proses Pengambilan Keputusan Pembelian Kerupuk Itik di Kabupaten Hulu Sungai Utara - Miranda Romaully Br. Sitanggang; Nidiya Dewi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2017)
This study aims to analyze the factors that influence consumers in making decisions to purchase duck crackers. The research was conducted in Amuntai City by collecting data using an accidental sampling method, which was met by 10 duck cracker sellers, of which 10 people were taken from 10 sellers. The research results of the characteristics of duck cracker consumers are housewives, fathers, students and adolescents. The survey results showed that the dominating consumers were 54 female sexes (67.5%). The results of the regression analysis of the coefficient of determination (R2) of the regression equation as a whole there are influences of independent variables including culture, social, individual, and psychological on purchasing decisions that can be seen in the adjusted R square value of 0.130. Factors that influence consumers in the purchase decision of duck crackers by 13% and 87% are influenced by other factors not included in the regression model. The regression test results are as follows: Y = 5.105 + 0.170X1 + 0.048 X2 + 0.119X3 + 0.306X4. Cultural, social and individual factors have no significant effect on the purchasing decision of duck crackers, while psychological factors influence the decision to purchase duck crackers in real time